Plastic deformation and hardening characteristics of the staggered zone under high in-situ stress unloading conditions - DUAN Shu-qian; GAO Po; JIANG Quan; ZHOU Yang-yi; XU Ding-ping (Rock and Soil Mechanics, 2022)
To clarify the plastic law and hardening characteristics of deformation and failure of staggered zone under high in-situ stress unloading conditions with excavation in underground engineering, a series of triaxial tests under different confining pressures and different loading and unloading stress paths was conducted. The plastic deformation laws of the staggered zone under different loading and unloading stress paths were deeply investigated. Based on the results of the experiments, the dependency of stress path of internal variables such as the equivalent plastic work, the equivalent plastic strain and the plastic volumetric strain as hardening parameters were further explored in the stress space. Meanwhile, a modified formula for hardening parameters with the independency of stress path was proposed. The results showed that, 1) The effect of stress path was significant on the deformation properties of staggered zone under high in-situ stress. The high initial confining pressure would inhibit the development of the circumferential plastic deformation of samples with the staggered zone under the same unloading stress path. And the plastic volumetric residual strain (6%) of samples with the staggered zone under the stress path of unloading axial pressure and confining pressure was significantly greater than that of other unloading stress paths (2%−4%) under the same initial confining pressure. The promoting effects of different stress paths on the plastic volumetric deformation of the staggered zone were as follows. The promoting effect of the stress path of unloading axial pressure and unloading confining pressure was the strongest, that of the stress path of constant axial pressure and unloading confining pressure was the second stronger, and that of the stress path of loading axial pressure and unloading confining pressure was the weakest. 2) There were a certain of the dependency of stress path of its internal variables such as plastic volumetric strain, equivalent plastic strain and equivalent plastic work during the deformation and failure process of the staggered zone in different unloading stress paths. Therefore, it is not accurate to directly take any of the above state parameters as the hardening parameters and assume that it is independent of the stress paths in the elastic-plastic analysis of staggered zone. Therefore, a modified method of the equivalent plastic work was proposed. It was found that when the parameter ns reflecting the material properties of staggered zone was equal to -0.4, the modified equivalent plastic work had the obvious independency of stress path, which was more appropriate for describing the unloading plastic strain hardening characteristics of the staggered zone under high in-situ stress unloading conditions. The plastic mechanical characteristics of the staggered zone revealed in this paper can further deepen the understanding of deformation and failure of the staggered zone under high in-situ stress unloading conditions, and provide a theoretical basis for the analysis of the failure mechanism and support control of the staggered zone in practical engineering.